The Effect of Concentration of Titanium Dioxide Nanoparticles on Their Antibacterial Activity in the Synthesis of Polyurethane Biopolymers - Andi Budirohmi; Yanti Mustari; Yunita Suriani; Vivi Adriana; Hasnah Natsir (Hydrogen: Jurnal Kependidikan Kimia, 2023)
In the health sector, the use of polyurethane (PU) as a basic material for medical devices still causes problems related to local and systemic infections. One of the most appropriate ways to overcome this problem is to synthesize PU biopolymer with titanium dioxide (TiO2) nanoparticles. The use of nano-shaped materials in this synthesis has many advantages, including being easier to synthesize and being antibacterial. Meanwhile, starch is the result of isolation from banana weevils, where banana weevils are agricultural waste that has not been utilized properly. Particle size and the use of agricultural waste are a form of modification and innovation in PU synthesis, as well as a novelty in the development of this research. In PU synthesis, several characterization techniques are carried out, including polymer tests, namely strain and stress, functional group analysis using (Fourier Transform Infra-Red), and antibacterial tests. Based on the results of the FTIR test analysis, it show that at a wave number of 1724.36 cm-1, the N-H functional group is visible, and the absorption of urethane and TiO2 groups is in the range of 513.07 cm-1. The mechanical properties test shows the strain (28.92 - 21.88% GL) and young's modulus in the interval (5.484-3.268 MPa). The antibacterial test showed that the inhibitory power of test samples A1 and A4 with diameters of 8 mm and 8 mm proved to be very effective in killing E. Coli bacteria, while test samples A1¹, A2¹, A3¹, and A4 were not able to kill E. Coli bacteria. S. Aureus. bacteria. The characterization results show that PU biopolymer can be used as a basic material for making bacterial decontaminant medical devices.